Establishment of the risk assessment method for food disinfectants and its application in China - YANG Daoyuan; WANG Yeru; BAI Li; XIAO Xiao; XU Haibin; LIU Zhaoping; ZHANG Lei; YONG Ling; SUI Haixia (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo establish the risk assessment method of food disinfectant with the peroxyacetic acid disinfectant for poultry slaughtering and processing as the model disinfectant.MethodsReferring to the risk assessment methods of food disinfectants from international organizations， the risk assessment method of food disinfectants suitable for China was established by considering the health effects， efficacy， and antimicrobial resistance. The safety of peroxyacetic acid disinfectant used for carcass disinfection during poultry slaughtering was assessed using the established method.ResultsUnder the setting condition， the health risk of the ingredients of the peroxyacetic acid disinfectant （peroxyacetic acid， acetic acid， hydrogen peroxide， and 1-hydroxyethylidine-1，1-diphosphonic acid） and the disinfection byproducts and reaction products after the treatment did not need priority attention. Based on the literature search results， the use of peroxyacetic acid disinfectants may not lead to decreased efficacy of fungicides and/or be associated with antimicrobial resistance.ConclusionThe risk assessment method for food disinfectants in China was established， which can be used as a methodological reference for the safety assessment of the new food disinfectant products in the future.